A Comparative Study the Calculation of the Optical Gap Energy and Urbach Energy in Undoped and Indium Doped ZnO Thin Films - Said Benramache; Boubaker Benhaoua; Okba Belahssen (Журнал нано- та електронної фізики)
In the present paper, we investigated a new model by theoretical methods; it is based on correlation from the experimental data’s which was used in the calculation the optical gap energy and Urbach energies. These data’s were taken from papers previously published. The choice ZnO thin films and spray only to compare our models with the Indium doping. From obtained relations found that the experimental data and theoretical calculation are in qualitative, which were supported with the variation of solution molarities and Indium doping. We have obtained a high correlation coefficient in the estimation of the band gap energy is higher than 0.96 with compare of Urbach energy is changed from 0.84 to 0.89. The measurements by these new models have agreed with minimum relative errors, it is found in the calculations of optical band gap does not exceed 4 %, and for Urbach energy are smaller than 20 and 10 % for undoped and Indium doped ZnO films, respectively. So that the best estimation was found at the Indium doped ZnO thin with maximum enhancement of minimum errors were limited to 3.5 and 9.7 % for the band gap and the Urbach energies, respectively. The decreases in the relative errors of undoped to Indium doped films can be explained by the fewer defects and less disorder.